Agriculture for Jobs and Growth in the Western Balkans : A Regional Report - World Bank (World Bank, Washington, DC, 2019)
The agri-food industry, comprising agricultural inputs, primary agricultural production, off-farm food processing, food distribution, food retail and consumption, and other food-related services, is one of the most important industries in the Western Balkans in terms of turnover, jobs and geographic scale. Average turnover of the agri-food industry accounts for 24 percent of total manufacturing turnover in the Western Balkan (WB) region compared to the European Union (EU) average of 15 percent (in 2011) and it is more evenly distributed geographically than other industries. Global evidence suggests that agribusiness has the highest short-term indirect employment impact, where creating one job generates more than double the number of jobs in the rest of the economy. The sector’s broad geographic footprint, multiple functions and cross-sector linkages could transform the industry into a powerful driver of value addition, income diversification and innovation in rural areas. The objective of this regional study is to examine how further investment, modernization and transformation of the agriculture and rural economy can contribute to job creation and economic growth in the Western Balkans, while highlighting how better public policies and deeper European integration can help take this process forward. The study aims to better understand the features of agri-food employment in the region, including its potential to generate more, better and more inclusive jobs and to identify transformative (policy) actions that could trigger a structural change towards a more productive use of human and other resources in agriculture.